Hubungan Indeks Massa Tubuh Dengan Kejadian Shivering Post Anestesi Spinal Pada Pasien Sectio Caesarea Di RSKDIA Siti Fatimah Makassar - Muhammad Hafiduddin; Mustika Sari; Asdar Asdar (Journal Pharma Saintika, 2021)
Background back : Shivering is frequent complications _ occur on technique spinal anesthesia . Index mass body low will more easy lost hot so that body compensate to drop temperature body for increase production hot and is factor risk happening possible hypothermia _ trigger incident intraoperative shivering Purpose : Knowing connection index mass body with incident shivering on patient Sectio Caesarea with spinal anesthesia , knowing frequency index mass body and shivering incident know _ level closeness connection as well as knowing factor risk index mass body with incident shiveringMethod : Observation analytic with approach cross sectional . Technique taking sample use purposive sampling. Sample study as many as 66 respondents and use test Chi Square.Result : Index mass body not enough with incident shivering as many as 9 (90%) respondents while those who are not shivering are 1 (10%) respondents , index mass body more with incident shivering 6 (20.7%) respondents while those who don't shivering 23 (79.3%) respondents , and index mass normal body with incident shivering 19 (70.4%) respondents while those who don't shivering 8 (29.6%) respondents .. Results test statistics use test Chi Square that is value 0.000 ( < 0.05 ) .Conclusion : There is connection Among index mass body with incident shivering on patient Sectio Caesarea with spinal anesthesia . Respondent part big have index mass body partially normal big experience shivering . Closeness level connection currently because other factors that can influence Shivering incident other than index mass body like , amount bleeding , duration of operation , length of fasting , temperature room and temperature preoperative body . _ Respondent with index mass body thin more risky experience intraoperative shivering _.